Stadt als Schule Nachbarschaftszentrum und Gemeinschaftsschule an der alten Feuerwache in Anger-Crottendorf, Leipzig. - Brecht, Norma (HTWK Leipzig - OA-Hochschulverlag, 2019)
When a fire department called "Ostwache" in the eastern part of Leipzig closed down, it left their old building behind vacant. Soon after a neighbourhood initiative sought to use the space to establish a community center for the surrounding neighbourhood. At the same time, the municipal government was planning a new school on the same lot. This thesis presents a solution for this conflict. By bringing together architectural, urban planning and pedagogical perspectives, while aiming for synergies. Following the model of Freinet pedagogy, a community school was planned with a new building at the site of the old fire station and the community center is to be located in the existing building of the old Ostwache. Through a common courtyard, shared work and sports facilities and a shared lunch, the school opens up to the city and its neighborhood to the school. This is how city works as school and a school works as city.